Clue Cells and Pseudo Clue Cells in Different Morphotypes of Bacterial Vaginosis - Swidsinski, Alexander; Loening-Baucke, Vera; Swidsinski, Sonja; Sobel, Jack D.; Dörffel, Yvonne; Guschin, Alexander (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Clue cells (epithelial cells heavily covered with adherent bacteria) are an accepted clue to the diagnosis of bacterial vaginosis. However, the exact morphologic criteria of clue cells and bacterial adherence were never elaborated. Materials and Methods We investigated adhesive and cohesive patterns of main microbiota groups in vaginal discharge using fluorescence in situ hybridization (FISH). Samples from 500 women diagnosed with bacterial vaginosis and positive for clue cells with classic microscopy were collected from 42 gynecologic practices in Berlin and reexamined in our FISH laboratory for the spatial distribution of Bifidobacteriaceae, Gardnerella, Fannyhessea vaginae (Atopobium); low G+C (guanine+cytosine) bacteria, lactobacilli, Lactobacillus iners; Lactobacillus crispatus, Gamma-Proteobacteria; and Enterobacteriaceae, Prevotella–Bacteroides, Veillonella, and Coriobacterium groups. Results Bacterial taxa present in vaginal smears were not accidentally assembled according to their relative abundance but were built in group-specific distribution patterns, which can be well described by two features: cohesiveness to each other and adherence to epithelial cells. Accordingly, four patterns can be distinguished: dispersed (non-adherent bacteria), dispersed adherent bacteria, cohesive (non-adherent) bacteria, and cohesive adherent bacteria. Direct cohesive adherence to the epithelial cells representing true clue cells was unique for Gardnerella species and observed only in 56% of the investigated samples. In the remaining vaginal samples, the epithelial cells were mechanically entrapped in bacterial masses, and the composition was unrelated to the epithelial cell surface, building non-adherent pseudo clue cells. The proportion of women with true clue cells in their samples from different gynecologic practices varied from 19% to 80%. Discussion Taxon indifferent imaging is inadequate for the exact analysis of the microbial layer adjacent to the vaginal epithelial cells. Morphologically seen bacterial vaginosis is a mix of at least two different conditions: biofilm vaginosis and bacterial excess vaginosis.